The Whore of Babylon. The reinvention of the apocalyptic symbol in the audiovisual - Martínez Fernández, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
A good part of the visual contemporaneity is the result of a reconfiguration of formal elements of the past. In this context is the Whore of Babylon, a biblical iconographic type that has been reinterpreted through Daenerys Targaryen in the audiovisual, specifically in the TV series Game of Thrones.